2017
DOI: 10.1016/j.jtcvs.2017.03.154
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral near-infrared spectroscopy insensitively detects low cerebral venous oxygen saturations after stage 1 palliation

Abstract: Cerebral rSO in isolation should not be used to detect low ScvO, because its sensitivity is low, although correction of rSO for arterial contamination may improve sensitivity. Cerebral rSO of 50 or greater should not be considered reassuring, though values below 30 are specific for low ScvO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…A further addition to the literature on comparisons between ScO 2 and directly measured ScvO 2 confirmed previous work that indicated that ScO 2 in isolation should not be used to detect low ScvO 2 , due to low sensitivity. They specifically concluded that a ScO 2 value of >50% should not be considered reassuring, given their findings.…”
Section: Perfusion Adequacysupporting
confidence: 79%
“…A further addition to the literature on comparisons between ScO 2 and directly measured ScvO 2 confirmed previous work that indicated that ScO 2 in isolation should not be used to detect low ScvO 2 , due to low sensitivity. They specifically concluded that a ScO 2 value of >50% should not be considered reassuring, given their findings.…”
Section: Perfusion Adequacysupporting
confidence: 79%
“…35 In a recent study building on this concept, Rescoe et al investigated the sensitivity of ScO 2 to screen for compromised tissue oxygen delivery (DO 2 ) defined as a SvO 2 <30% in neonates following stage 1 palliation for HLHS. (49) The main finding of this study was an insensitivity of cerebral oximetry in detecting a SvO 2 <30% in the ScO 2 range of clinical interest (i.e. ScO 2 30-50%).…”
Section: Cerebral Oxygen Saturation In Chdmentioning
confidence: 64%
“…(48) In a recent study building on this concept, Rescoe et al investigated the sensitivity of ScO 2 to screen for compromised tissue oxygen delivery (DO 2 ) defined as a SvO 2 <30% in neonates following stage 1 palliation for HLHS. (49) The main finding of this study was an insensitivity of cerebral oximetry in detecting a SvO 2 <30% in the ScO 2 range of clinical interest (i.e. ScO 2 30-50%).…”
Section: These Findings Have Important Implications When Interpretingmentioning
confidence: 64%